The Hospitality: Does It Affect Audit Independence? Auditor vs. Auditee Perspective - Setiawan, Nanang (Sekolah Tingg Ilmu Ekonomi Y.A.I Jakarta - Indonesia, 2024)
This paper aims to analyze the impact of hospitality on independence and audit quality based on the viewpoints of the auditor and auditee. This paper is qualitative research with data collection by observation and semi-structured interviews with internal auditors and financial managers (auditees) at multinational companies in Indonesia. The results of the analysis state that there are similarities in views between auditors and auditees regarding hospitality. Auditors consider that hospitality, although it cannot be generalized to all auditors, will not interfere with their independence in the audit process and assessment of audit results. The auditee is also of the view that hospitality is one aspect of service from the